Dislocation kinetics during plastic deformation of two-dimensional polycrystals - Badiyan, E.E.; Tonkopryad, A.G.; Ftomov, Ye.V.; Shekhovtsov, O.V. (Вопросы атомной науки и техники, 2019)
The dislocation-kinetic approach is applied to the study of plastic flow of plate specimens of two-dimensional polycrystals of high purity metals under uniaxial tension with a constant strain rate at moderate temperatures. A dislocation-kinetic equation is formulated. It takes into account the role of the free surface of a plate specimen, which is the source and sink of dislocations, and the strengthening effect of through grain boundaries in a twodimensional polycrystal. To calculate tensile stress-strain curves, the kinetic equation was transformed using the Taylor strain hardening law and an analytical solution was obtained for this equation. Using the example of plate specimens of two-dimensional polycrystals of high purity aluminium (99.999 at.%) it was shown that the calculation results are in good agreement with experimental data. Дислокаційно-кінетичний підхід застосовано до дослідження пластичної течії плоских зразків двовимірних полікристалів чистих металів в умовах одноосного розтягу з постійною швидкістю деформації при помірних температурах. Сформульовано дислокаційно-кінетичне рівняння, в якому враховані роль вільної поверхні плоского зразка, яка є джерелом і стоком дислокацій, і зміцнююча дія наскрізних меж зерен у двовимірному полікристалі. Для розрахунку кривої деформації кінетичне рівняння перетворено з використанням закону деформаційного зміцнення Тейлора і отримано аналітичне рішення цього рівняння. На прикладі плоских зразків двовимірних полікристалів чистого алюмінію (99,999 ат.%) показано, що результати розрахунків досить добре узгоджуються з експериментальними даними. Дислокационно-кинетический подход применен к исследованию пластического течения плоских образцов двумерных поликристаллов чистых металлов в условиях одноосного растяжения с постоянной скоростью деформации при умеренных температурах. Сформулировано дислокационно-кинетическое уравнение, в котором учтены роль свободной поверхности плоского образца, являющейся источником и стоком дислокаций, и упрочняющее действие сквозных границ зерен в двумерном поликристалле. Для расчета кривой деформации кинетическое уравнение преобразовано с использованием закона деформационного упрочнения Тейлора и получено аналитическое решение этого уравнения. На примере плоских образцов двумерных поликристаллов чистого алюминия (99,999 ат.%) показано, что результаты расчетов достаточно хорошо согласуются с экспериментальными данными.